Electrostatically induced mixing in confined stratified multi-fluid systems - Cimpeanu,R; Papageorgiou,DT (International Journal of Multiphase Flow, 2015)
Electrostatic control mechanisms underpin a wide range of modern industrial processes, from lab-on-a-chip devices to microfluidic sensors for security applications. During the last decades, the striking impact of fluid interface manipulation in contexts such as polymer self-assembly, micromanufacturing and mixing in viscous media has established the field of electrically driven interfacial flows as invaluable. This work investigates electrostatically induced interfacial instabilities and subsequent generation of nonlinear coherent structures in immiscible, viscous, dielectric multi-layer stratified flows confined in channels with plane walls. The present study demonstrates theoretically that interfacial instabilities can be utilized to achieve efficient mixing in different immiscible fluid regions. This is accomplished by electrostatically driving stable flows far from their equilibrium states to attain time-oscillatory and highly nonlinear flows producing mixing. The nonlinear electrohydrodynamic instabilities play the role of imposed background velocity fields or moving device parts in more traditional mixing protocols. Initially, simple yet efficient on–off voltage protocols are investigated and subsequently symmetry-breaking voltage distributions are considered and shown to considerably enhance the achieved level of mixing. Both two- and three-dimensional flows, containing realistic fluid configurations (water and oils), are computed using direct numerical simulations based on the Navier–Stokes equations. Such numerical investigations facilitate the quantitative study of the flow into the fully nonlinear regime and constitute the basis of optimization methods in the context of microfluidic mixing applications in two- and three-dimensional geometries.